Search in e-Learning systems with semantic web technologies - Gonçalves, Vitor (2010)
The traditional view of learning puts most of the emphasis on face-to-face teaching and curriculum. It is very slow and expensive. Many people try to find e-Learning systems and learning objects on the Web. But that can be very difficult to find what we need with the actual search engines. How can someone quickly find and with meaning the learning objects existing in the Web? Use Semantic Web technologies and software agents to develop an search engine for the Semantic Web Infrastructure learning environments is the proposal of this poster.